ORGANOGENESIS TANAMAN BAWANG MERAH (ALLIUM ASCALONICUM.L) LOKAL NAPU SECARA IN VITRO PADA MEDIUM MS DENGAN PENAMBAHAN IAA DAN BAP - Utami, Felma Tri; Haliani, Haliani; Muslimin, Muslimin; Suwastika, I Nengah (Natural Science: Journal of Science and Technology, 2013)
The aims of this study were to find out the optimum combination of IAA and BAP hormones in MS based medium, which suitable for promoting in vitro-organogenesis. In vitro experiment on inducing organogenesis of Shallot c.v. Local Napu showed that combination of 0.01 ppm IAA and 1 ppm BAP, it was the best combination on MS based medium for that organogenesis. These result was based on the measurements over several parameters, including: period of emerging shot and root, precentage of explant growth, number of roots, number of leaves, number of stomata, also chlorophil content of planlet leaves. This data suggesting that MS medium containing 0.01 ppm IAA and 1 ppm BAP was a potential medium to be used on propagation of shallot c.v. Local Napu.